2014
DOI: 10.5430/jnep.v4n4p120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating preceptors’ and preceptees’ satisfaction concerning preceptorship and the preceptor-preceptee relationship

Abstract: Background: Retention of newly graduated nurses is becoming a costly challenge regardless of efforts such as orientation and residency programs. Satisfaction with the preceptorship relationship is important if the preceptor is to remain committed to fulfilling the role and if the preceptee is to complete the experience and then exhibit satisfactory clinical performance. Most studies have focused on describing either preceptor or preceptee perspectives regardless of the fact that both parties impact the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The relationship between the graduate nurse and preceptor was evaluated using the Preceptor/Preceptee Satisfaction Questionnaire [18]. Graduate nurses generally rated the graduate/preceptor relationship highly (range 76.7—87.5), and reported having a preceptor who was available, encouraging, supportive, open, willing to share knowledge, and with whom they felt comfortable (Table 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the graduate nurse and preceptor was evaluated using the Preceptor/Preceptee Satisfaction Questionnaire [18]. Graduate nurses generally rated the graduate/preceptor relationship highly (range 76.7—87.5), and reported having a preceptor who was available, encouraging, supportive, open, willing to share knowledge, and with whom they felt comfortable (Table 9).…”
Section: Resultsmentioning
confidence: 99%
“…1) Six Dimension Scale of Nursing Performance [16] which assessed the graduate nurse and preceptors’ perceptions of the graduate’s nursing competency; 2) Casey-Fink Graduate Nurse Experience Survey [17] which assessed the graduate’s perceived confidence; 3) Preceptor/Preceptee Satisfaction Questionnaire [18] which assessed graduates and preceptors' perceived satisfaction with the preceptor/graduate relationship in terms of preceptor behaviours; 4) Halfer-Graf Job/Work Environment [19] which assessed graduate's satisfaction with the program; and 5) Nurse Entry to Practice Program Evaluation [20] which assessed graduate nurses experiences of the program including rotations and their preceptor. A summary of these tools including alterations for use in this study, and when and to whom tools were administered is presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In critical care nursing fields, several models for new graduate and novice nurse transition exist with differing degrees of effectiveness (Edwards, 2015;Farnell and Dawson, 2006;Haggerty et al, 2013;Hyrkas et al, 2014;Kaddoura, 2010). Educational support frameworks in nursing are inconsistent (Wolak et al, 2009) and vary in duration, structure, program components, rotations, financial support and content (Edwards, 2015;Rush et al, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…When preceptor training was offered in one study, multiple preceptors reported not being able to attend due to workload and patient acuity issues in their workplace (Haggerty et al, 2013). Another study highlighted similar issues with less than half of the preceptors attending training, however the authors did not comment why (Hyrkas et al, 2014). Preceptor training was reported to be anywhere from a few hours to more extensive ongoing development programs.…”
mentioning
confidence: 99%